Amoebiasis: a rare cause of cardiac tamponade. - Gomersall, L. N. (1994)
Cardiac tamponade secondary to perforation of a hepatic amoebic abscess developed six years after the patient had visited an area where Entamoeba histolytica is endemic. He was treated with metronidazole and imipenem, emergency percutaneous catheter drainage, and open surgical drainage.